Using engineering remote laboratories to enhance student learning - A distributed learning experience - Eleftheriou, Polyvios; Michaelides, Ioannis (My University, 2009)
We present our experience of the operation of the solar energy e-learning laboratory (Solar e-lab) in Cyprus, and demonstrate the benefits of distributed learning by employing a remote engineering application. We focus on experientially-based learning which allows remote and distributed training with laboratories, workshops and real working-places over the Internet. The aim of the solar energy e-learning laboratory is to use today's technology as a tool to make laboratory facilities accessible to engineering students (especially handicapped) and technicians located outside the e-lab premises. In this way, the laboratory, its equipment and experimental facilities can be shared by many people, thus simplifying availability and widening educational experiences. Over its four years of operation, users from more than 400 locations in 75 countries have visited the solar e-lab. The results of an online evaluation showed a high degree of satisfaction by the remote students using the solar e-lab. Also, a number of foreign educational Institutions of higher learning have included the solar e-lab in their curricula. © 2009 TEMPUS Publications.
Keywords: Distributed learning; E-learning; Internet; Real world experiments; Remote engineering; Remote laboratories; Solar energy